Pengujian Sistem Pendukung Keputusan Penjurusan SMA di Banten menggunakan Metode Black Box - Tri Yani Akhirina; Dwi Yulistyanti; Ana Rusmardiana; Ulfa Pauziah (Ikatan Ahli Informatika Indonesia (IAII), 2018)
Abstract The Decision Support System (DSS) of SMA major which had been tested in Banten was a system obtained from the former research, as it was expected to help private schools in Banten for students' major. This system has been developed through Fuzzy Tsukamoto's method in obtaining students' major. Fuzzy Tsukamoto requires three determinant factors, namely: skill, interest and aptitude. Fuzzyfication is carried out to get a firmed score of IPA and IPS. After the two scores are obtained, the comparison of those highest scores is conducted to determine the recommendation. In the process of manual data testing, Fuzzy Tsukamoto can be applied in students' major in Banten, with 98% of its accuracy level. After manual testing, Decision Support System of SMA major is designed by using Research and Development (R & D) as its developing system and by Unified Modeling Language (UML) as its designing analysis. The objective of this research aims at measuring the quality testing process of the application that is based on the aspects of functionality, reliability, usability, dan efficiency testingby employing the black box method. Based on the measurement Black Box Method, the Decision Support System of SMA major gets very goodvield, as it can be applied to be as SMA major recommendation in Banten.